Rancang Bangun Aplikasi Pembukuan Koperasi Simpan Pinjam Berbasis Web Menggunakan Metode Extreme Programming - I Komang Yoga Gangga Putra; I Nyoman Yudi Anggara Wijaya; Anak Agung Gede Adi Mega Putra (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
The development of digital technology has significantly impacted the efficiency of financial management, including in savings and loan cooperatives. However, the Bali Provincial Health Department Cooperative still faces challenges such as manual bookkeeping, which is prone to errors, delays in data processing, and difficulties in presenting accurate financial reports. This study aims to design and implement a web-based accounting application using the Laravel framework and MySQL database to automate loan calculations, data storage, and real-time report generation. The system development adopts the Extreme Programming (XP) methodology, which emphasizes short iterations, intensive user communication, continuous testing, and the application of simple design principles to ensure software quality. Testing results indicate that the application can reduce bookkeeping errors, accelerate report generation, and provide cooperative members with quick and accurate access to financial information. The contribution of this study is to offer a digital solution that enhances accuracy, efficiency, and transparency in cooperative financial management, while also supporting the development of local microenterprises.